A new biological assay of Aβ clearance: The Aβ mid‐domain immunoassay: Development of new models and analysis methods/amyloid/Aβ. (7th December 2020) - Torsetnes, Silje Bøen; Wettergreen, Marianne; Nordengen, Kaja; Gisladottir, Berglind; Sharma, Kulbhushan; Christensen, Erik; Fladby, Tormod
Abstract: Background: Decreased Aβ clearance is thought to precede the clinical AD symptoms by a decade or more. Clearance of Aβ include phagocytosis and degradation are two important components. Innate immune‐linked genetic risk factors contribute to AD, and innate immune cells – microglia in the brain and monocytes/macrophages in the peripheral blood – phagocytize and degrade Aβ. Based on this, we hypothesize that intra‐ and extracellular Aβ fragments, specifically mid‐domain Aβ, reflect phagocytic activity or Aβ degradation efficiency. Our objective was thus to develop an assay measuring intra‐ and extracellular Aβ mid‐domain peptides in relevant biological specimens. Method: Firstly, a panel of sheep monoclonal antibodies (mAbs by Bioventix Ltd, UK) was raised against the Aβ20‐34 peptide. Secondly, an anticomplex antibody (HuCal, BioRad, CA, USA) was screened for, needing to be selective for only Aβ20‐34 bound to the most sensitive sheep mAb. Throughout these processes, immunoprecipitation and reversed phase liquid chromatography mass spectrometry (IP LCMS) were used to map the affinity and selectivity of the best performing antibodies pair (sheep mAb 2A9 and HuCal H3). Thirdly and finally, an immunoassay on the Quanterix Single Molecule Array (Simoa, Quanterix, MA, USA) platform was developed, resulting in our final product. Result: IP LCMS experiments showed that sheep mAb 2A9 bound to a mid‐domain peptide is needed for complex formation with HuCal H3. In selectivity mapping, where endogenous Aβ was screened for in CSF using these antibodies in a sandwich, a preferential binding of AβX‐34>>AβX‐40 was demonstrated. The two antibodies applied in a new immunoassay on the Simoa platform, gave a sensitive immunoassay detecting Aβ mid‐domain peptides with a LOD<0.5 pg/ml. Thus detecting endogenous levels both in CSF and in blood derived samples such as serum, plasma and monocyte lysates. Various samples from healthy subjects, study participants in AD intervention studies, and other clinical samples are currently being analyzed. Conclusion: Here, we present the first immunoassay able to detect endogenous catabolic Aβ peptides in a range of biological tissue fluids. This functional assay thus paves the way for novel studies on Aβ clearance and catabolism and may serve as a tool for peripheral blood measurement in both disease progression‐ and intervention studies.